Responsibility Under Uncertainty: Which Climate Decisions Matter Most? - Nicola Botta; Nuria Brede; Michel Crucifix; Cezar Ionescu; Patrik Jansson; Zheng Li; Marina Martínez; Tim Richter (Environmental Modeling & Assessment, 2023)
We propose a new method for estimating how much decisions under monadic uncertainty matter. The method is generic and suitable for measuring responsibility in finite horizon sequential decision processes. It fulfills "fairness" requirements and three natural conditions for responsibility measures: agency, avoidance and causal relevance. We apply the method to study how much decisions matter in a stylized greenhouse gas emissions process in which a decision maker repeatedly faces two options: start a "green" transition to a decarbonized society or further delay such a transition. We account for the fact that climate decisions are rarely implemented with certainty and that their consequences on the climate and on the global economy are uncertain. We discover that a "moral" approach towards decision making — doing the right thing even though the probability of success becomes increasingly small — is rational over a wide range of uncertainties.
Keywords: 690; Climate policy; Responsibility measures; Uncertainty; GHG emissions processes; Verified decision making